Thermoregulation and dehydration in athletes: recommendations and review - Carter, J. G.; Brooks, K. A. (Journal of Sport and Human Performance, 2013)
Numerous athletes experience some form of heat illness resulting in acute discomfort or distortion of physiological processes. Unfortunately, there are some athletes whose heat illness has caused chronic damage or even death. The purpose of this article was to review physiological mechanisms driving thermoregulation, and to summarize recent research articles on dehydration and performance in athletes. Safety recommendations based on this review include having weigh-ins before and after practice, having athletes monitor the color of their urine, and randomly measuring the urine specific gravity of athletes. Availability of water and formulated rehydrating beverages during sporting events is necessary, while monitoring all athletes during practices and competitions, and educating athletes on how to properly hydrate need to be emphasized. Further research regarding safety standards in extreme environments are needed to ensure the safety, health, and optimal performance of athletes.